Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kreatif Siswa pada Pembelajaran IPA - 'Adiilah, Ima Ishlahul; Haryanti, Yuyun Dwi (Papanda Journal of Mathematics and Science Research, 2023)
The purpose of this research is to identify, describe and analyze the results of several primary studies on the effect of the PBL model on the creative thinking skills in science. Systematic literature review (SLR) was used as the method in this study, through searches on the Google Scholar and DOAJ databases from 2018 to 2022, resulting in 15 primary studies that met the specified inclusion criteria. Each article was recorded and then classified based on title, year of study, level of education, and type of research to be analyzed one by one. The results showed that PBL had an influence on the development of students' creative thinking skills science learning, because with the PBL model the learning process applied student-centered problem-based learning activities with the teacher acting as a facilitator, and involving students in independent discovery activities through collaboration between students in small groups to solve problems representatively. So that PBL is suitable to be applied to achieve the goals and urgency of learning, especially in developing students' creative thinking skills.